The Role of Guidance and Counseling Teacher in Student Career Planning at Vocational High School: - - Ikawati Ikawati; Edhy Susatya; Muhammad Kunta Biddnika (Universitas Palan, 2026)
The role of guidance and counseling teachers in student career planning in vocational schools is still weak. The purpose of the study was to analyze the implementation of the BK service program in career planning for vocational school students. The study used a qualitative descriptive method. The study was conducted at SMK Muhammadiyah Paguyangan with research subjects being BK teachers, vice principals for curriculum, and vocational school students. Data collection through observation, interviews, and document studies. Data validation applied triangulation of sources and methods. Data analysis used the Atlas ti.8 application. Research stages; determining topics, compiling interview guidelines, selecting data collection methods, collecting data, analyzing data, and drawing conclusions. Research results; (1) the role of BK teachers in identifying students' potential, interests, talents, providing guidance in choosing education or careers, as motivators, facilitators, mediators, directors, program managers, and informants, (2) BK teacher strategies in student career planning; providing basic services to recognize self-potential, motivating, encouraging the use of technology, and digital platforms, and (3) implementation of BK programs through an integrated process, including; program planning, resource provision, implementation of evaluation services, feedback, and continuous improvement. Program innovation and monitoring are integral parts to maintain the relevance and effectiveness of BK services. The success of BK program implementation depends on the quality of coordination and commitment of all parties in developing the program.